Die strafbefreiende Wirkung präventiv erstatteter Rechtsauskünfte - Iversen, Katrina (Tectum Verlag, 2023)
Situations in which the citizen who is willing to act turns to a respondent, receives legal information that denies the wrongfulness of the act, acts in reliance on this information and the court later considers the act to be unlawful cause considerable difficulties. A particular challenge is posed by - practically relevant - cases in which the legal situation is unclear. Only if the person requesting information turns to a respondent from whom he can expect expert and objective information and he cannot see that he should not rely on the information, does he act blamelessly. In this volume, the author defines the circle of respondents and sets out formal and substantive requirements for legal information.